Education on Funeral Prayers in Pasar Tiga Village - Miswar Miswar; Mila Rosdiana Sianipar; Riska Tiara Putri; Febby Erna Sari Lubis (Edumaspul: Jurnal Pendidikan, 2022)
In this study, it is a type of research that directly educates about fardhu kifayah in the form of corpse prayers. Corpse prayer is one of the prayer practices carried out by Muslims if there are other Muslims who die. There are as many as two practices. The method used by researchers when they want to teach the right and appropriate way to carry out corpse prayers for mayit consists of several methods in the form of demonstrations, memorization, and lectures accompanied by the use of media to facilitate the delivery of material. After conducting education related to the implementation of fardhu kifayah in the form of corpse prayers, students of SDN 09 Panai Tengah can do well as taught and practiced. It was the same with the second time it was held at the Al-Falah mosque. Therefore, we as students of KKN-131 UINSU made an activity in the form of educating the prayers of the corpse so that students and children around Pasar Tiga Village would be biased towards petrification among the surrounding environment.